PENGARUH MEDIA PEMBELAJARAN PENGENALAN TATA CARA WUDHU DAN SHOLAT BERBASIS ANIMASI 3 DIMENSI TERHADAP HASIL BELAJAR FIQIH KELAS 1 MADRASAH IBTIDAIYAH NEGERI 1 KARANGASEM - Ahda Audia; Nyoman Sugihartini; I Made Putrama (Universitas Pendidikan Ganesha, 2019)
This study aims to determine (1) differences in learning outcomes between students using learning media introduction to procedures for ablution and prayer based on 3-dimensional animation and students using lecture methods (2) knowing student responses after using learning media introduction to procedures for ablution and prayer based 3-dimensional animation. This type of research is a quasi-experimental (quasi-experimental) design with Post Test Only Control Group Design. Learning outcomes data were analyzed by conducting normality tests, homogeneity tests and t-tests. The results showed that the average results of the analysis of learning (experimental> control) with cognitive values (81.46> 70), psychomotor values (95> 89.23), affective values (79.2> 70.83) and student responses from the application of learning media in Fiqh subjects is very positive, namely 21 out of 25 students. Keywords : Learning Media, Fiqh Learning Results, Student Response